1990
DOI: 10.1016/0735-1097(90)90655-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential enhancement of postischemic segmental systolic thickening by diltiazem

Abstract: Prolonged depression of segmental systolic thickening after brief coronary artery occlusion may result principally from events during reperfusion rather than during the ischemic interval. Thus, cellular calcium overload at reperfusion may be a mediator of contractile dysfunction after brief ischemia, and reduction of calcium entry by diltiazem, a calcium channel antagonist, may enhance recovery of systolic thickening after brief periods of ischemia. Thirteen awake unsedated dogs instrumented with hemodynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Taylor and colleagues [3] reported that diltiazem (15 ~g/kg/min), administered preocclusion, enhanced the recovery of wall thickening following 15 minutes of transient ischemia. Furthermore, Taylor…”
Section: Calcium Antagonists and Stunned Myocardium: Experimental Resmentioning
confidence: 99%
See 2 more Smart Citations
“…Taylor and colleagues [3] reported that diltiazem (15 ~g/kg/min), administered preocclusion, enhanced the recovery of wall thickening following 15 minutes of transient ischemia. Furthermore, Taylor…”
Section: Calcium Antagonists and Stunned Myocardium: Experimental Resmentioning
confidence: 99%
“…Ther 1991;5:947-952 During the two decades since the "stunned myocardium" was first documented, considerable investigative effort has focused on elucidating the cause or mechanism of this postischemic dysfunction and thereby identifying agents that might attenuate this phenomenon. Specifically, our laboratory and others found that the calcium-channel blocking agents verapamil [1], nifedipine [2], diltiazem [3], and amlodipine [4,5] significantly enhance the recovery of contractile function in dogs "stunned" by a brief episode of transient coronary artery occlusion. We were particularly interested to find that verapamil and nifedipine improved systolic contraction, even when treatment was "delayed," that is, when the agents were administered 30 minutes after reflow had been established [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…102], dipyridamole and nitroglycerin [102]. However, a Gregg phenomenon appears not to be the underlying mechanism for the improved functional recovery' of stunned myocardium after treatment with calcium antagonists since improved functional recovery was also observed in the absence of improved blood flow during reperfusion [83,86,91] and. on the other hand, a substantial increase in blood flow was not associated with improved functional recovery when the calcium antagonist nisoldipine was given after estab lished reperfusion [89] (fig.…”
Section: Improved Recovery O F St Aimed Myocardium By Calcium Antagonmentioning
confidence: 99%
“…Since gallopamil has no direct oxygen radical scavenging activity, its protective effect may be linked to a reduction of calcium overload [80], As in the in vitro studies, all in vivo studies using mod els of reversible damage with shortlasting myocardial ischaemia followed by reperfusion revealed improved recovery of regional contractile function when treatment with calcium antagonists was started before ischaemia [30,[81][82][83][84][85][86][87][88][89][90][91][92][93][94], Apart from two studies in anaesthetized pigs [81,94], all studies utilized anaesthetized [82-86, 88-90, 92. 93] or conscious [87,91] canine preparations. In a number of studies the improvement in regional contrac tile function was not fully convincing since arterial pres sure was also reduced by the calcium antagonists after intravenous administration [81.…”
Section: Improved Recovery O F St Aimed Myocardium By Calcium Antagonmentioning
confidence: 99%